An Operational Design Of Doppler Vhf Omni Directional Range (DVOR) Based On Virtual Reality As A Learning Media At Medan Aviation Polytechnic - Jesica Uli Panggabean; Bela Firmantoyo; Darmeli Nasution (Jurnal Scientia, 2024)
Information and communication technology has experienced rapid development, which can be utilized in the field of education. This final project aims to design the virtualization of the Doppler VHF Omni-Directional Range (DVOR) operating procedure based on Virtual Reality (VR) as a learning medium for students of the Air Navigation Engineering Program at Medan Aviation Polytechnic. This virtualization is expected to provide a learning experience that closely approximates reality, facilitating the understanding of the DVOR concept and function, which is often difficult to explain verbally. This research employs software design and development methods, where the VR DVOR is designed using Unity 3D and the Oculus Quest VR Headset. The research results indicate that using VR as a learning medium positively affects students' understanding of the DVOR operating mechanism. Moreover, VR provides students the opportunity to perform interactive and realistic simulations of DVOR operations, which are challenging to conduct with physical equipment directly. The benefits of this research include creating innovation in practical learning methods, enhancing students' understanding of air navigation equipment, and developing better technical skills. It is hoped that the results of this final project can serve as a reference for developing other VR-based learning media in the field of air navigation.